O tragičnem danes - iz perspektive subjekta in situacije - Kozak, Krištof Jacek (Primerjalna književnost, 2003)
On the Tragic Today: From the Perspective of the Subject and the Situation. The article traces the influence exerted by the Aristotelian tenets of tragedy, thus emphasizing the issue of the paradigmatization of Poetics. It demonstrates the manner in which the history of tragedy in the West has emerged in light of this foundational treatise. In relation to contemporary forms of tragedy, the article further discusses the institutionalization of the subject's disappearance in post-structuralist hypotheses, together with a new basis for the self-reconstitution of the subject developed by philosophers such as Lévinas. The argument endorses the contemporary view of tragedy, which it sees as a dramatic, conflictual situation that is compelled to meet two additional conditions: it has to be at once unavoidable and irresolvable.
Keywords: Aristoteles, 384-322 pr.n.št.; tragedija; Lévinas, Emmanuel, 1905-1995; teorija tragedije; tragično; poststrukturalizem; subjekt